Multicriteria analysis of sustainable agri-food waste management for an agroecosystem in Finland - Marttila, Miika; Havukainen, Jouni; Uusitalo, Ville; Linnanen, Lassi; Mikkilä, Mirja (Frontiers in Sustainable Food Systems, 2024)
The heavy reliance on fossil inputs of agricultural practices has led to maximizing yields and profitability, even at the expense of environmental sustainability. Implementing circular waste management solutions could help align the economic and environmental goals of farmers while reducing their reliance on fossil inputs. The co-application of anaerobic digestion and pyrolysis has been recognized as a potential solution to assist in the transition towards sustainable agriculture. This research assesses different waste management strategies of the major sidestreams generated in agroecosystems in Finland from a climate impact and financial perspective, particularly focusing on the integration of anaerobic digestion and pyrolysis as an emerging solution. Six waste management options representing manure application, composting, incineration, anaerobic digestion, pyrolysis, and a co-application process of anaerobic digestion and pyrolysis, are simultaneously assessed with cash flow analysis and life cycle assessment. The results indicate that co-applying anaerobic digestion and pyrolysis strengthens the performance of a farm through reduced impact on climate, diversified revenue streams, and increased security of supply, even though the direct, short-term financial benefits remain marginal. The capability of co-application of anaerobic digestion and pyrolysis to reduce the climate impacts within the studied system supports the consensus that sustainable and self-sufficient agroecosystems could be supported by this solution in the future. The adoption of more sustainable agricultural practices requires further development of technologies and additional value creation mechanisms, such as stronger employment of carbon markets, to even the economic competition and favor low-carbon operations for practitioners.